El diccionari de l'Institut d'Estudis Valencians de 1937 - Emili Casanova (Caplletra: Revista Internacional de Filologia, 2015)
In this article Casanova uses various archives –in particular that of Emili Beüt i Belenguer– to reconstruct the process of elaborating the general dictionary of Valencian. This dictionary was written during the Spanish civil war through the IEV, an organization in which Salvador played a decisive role. The author presents several dictionary entries and compares them with others from Pompeu Fabra's DGLC, and with other works.